AVTOMATLAŞDIRILMIŞ İDARƏETMƏ SİSTEMLƏRİNİN SƏNAYE MÜƏSSİSƏLƏRİNDƏ ÇÖRƏKBİŞİRMƏ PROSESLƏRİNİN OPTİMALLAŞDIRILMASINDA TƏTBİQİ. - Abduləzizova, Sevinc; Cəfərov, Elman (History of Science (2790-0029), 2026)
The bakery industry is one of the most important branches of the food industry, providing the population with valuable food products. In order to increase production efficiency and product quality, automated control systems (ACS) are widely used in bakery enterprises. This article examines the application of ACS to optimize baking processes in industrial enterprises. The main stages of the technological process of bakery products production are analyzed. These stages include receiving and storing raw materials, dosing and mixing of ingredients, kneading, dividing and forming dough, proofing, baking and cooling of the finished product. The main factors affecting the technological process and the quality of the final product have been identified. These include temperature, humidity, storage time at separate stages, and other indicators. It is explained how these parameters are controlled and regulated by automated control systems (ACS). During the study, technical documents related to ACS used in bakery enterprises were studied, the experience of applying these systems in production was investigated, and their impact on product quality was practically verified. More accurate measurement of the main raw materials with automatic dispensers, correct maintenance of temperature and humidity during dough fermentation and baking, as well as precise time control at process stages have been studied. The conducted studies have shown that the application of AIS makes the production process more stable and significantly improves the quality of bakery products. Thus, reducing the error in flour dosing to ±1% leads to a deviation of the dough moisture content from the given indicators by an average of 0.3--0.5%. Correct regulation of the dough fermentation and bread baking processes increases the volume of products by 10--15% and improves the structural and mechanical properties of the interior. It has also been determined that the use of automated control systems reduces raw material and finished product losses by 5--7%, reduces energy consumption by 8--12%, and increases the productivity of technological lines by 10--15% compared to traditional control methods. Therefore, the results of the conducted studies show that the application of AIS is very effective in optimizing baking processes in industrial enterprises. The developed recommendations can be used to increase the quality and competitiveness of bakery products during the application and use of these systems.